Assessment of methods to reduce lower back, neck and shoulder pain discomfort scores and their range of motion among office workers - Shariat, Ardalan (2016)
Background: Musculoskeletal discomforts (MSD), especially in the neck, lower back and shoulder areas, are some of the most common issues among office workers. The actual number of cases of musculoskeletal injuries/pain among Malaysian office workers is suspected to be much higher than the 10,000 cases claimed by SOCSO. MSD can lead to uncomfortable working conditions and subsequently lead to absenteeism as well as an increasing need to obtain medical certificates (MCs) among office workers during working hours. This is because of the physical pain/injuries caused by MSD, and these have a negative effect on the productivity and financial efficiency of companies/employers. A practical and cost-efficient treatment, without side effects, can be a helpful way to improve the productivity and financial efficiency of companies by reducing MSD-induced staff absenteeism. Objectives: The three primary aims of this research were to: 1. Measure the incidence of MSD in a sample of office workers; 2. Test effective methods of reducing lower back, neck and shoulder pain in this sample by training exercise, or ergonomics modification, or both of them; and 3. Assess discomfort scores and the range of motion of the lower back, neck and shoulder muscles among the office workers after undertaking the different methods for a period of 6 months. Methods: In a true experimental design, from 10,000 office workers of a selected company in Malaysia, 142 office workers (of whom 50 were male), aged between 20- 50 years, who had MSD with medium/ high severity of pain and had volunteered to participate in this study, were allocated randomly, from 3 different locations (Bangsar, Puchong, and Damansara), to one of three intervention groups (receiving training exercise, receiving modified ergonomics, receiving a combination of exercise and ergonomics modification) and a control group (receiving none of these interventions). The Cornell MSD Questionnaire was used to measure musculoskeletal discomforts, with focus on pain severity, before treatment and after 2, 4 and 6 months of the interventions. The range of motion (ROM) of the hip, neck, shoulder and knee were measured by a 30cm goniometer, and the Borg CR10 scale was used to measure the perceived exertion of training exercises. The rapid office strain assessment (ROSA) questionnaire was used to assess the strain associated with office work. Height and weight were also measured to calculate the body mass index (BMI). Results: MSD was common and it was most frequent in the regions of the shoulder, neck, and lower back with high level in severity of pain. The mean value for ROM (pre- to post-intervention changes) in the hips and knees in the exercise (right hip: from 71±12 degree to 87±5 degree, left hip: from 71±11degree to 88 ±3 degree; right knee: from 153±20 degree to 169±15 degree, left knee: from 150±20 degree to 164±18 degree (mean±SD)) and exercise + ergonomics modification groups (right hip: from 71±11degree to 86±5 degree, left hip: from 72±10 degree to 85± 6 degree; right knee: from 153±19 degree to 172±11 degree, left knee: from 151±2 degree to 169±13 degree (mean±SD)), but the ROM of the neck and shoulder were improved also in the ergonomics group significantly ((p<0.05). MSD mean value scores related to neck, shoulder and lower back decreased significantly (p<0.05) in all three intervention groups. ROSA mean value scores decreased significantly (p<0.05) only in the ergonomics modification and exercise + ergonomics modification groups. The Borg scale results showed acceptable levels of perceived exertion related to the exercise package. Conclusion: 6 months of training exercise is able to increase the range of motion and it can be helpful in decreasing the prevalence of MSD. Ergonomic modifications are another way to decrease MSD rates by correcting the postures of office workers. A mixture of training exercise and ergonomic modifications can be more effective in lowering MSD rates, as it can also improve the ROM and working posture.